OPTIMALISASI KETERLIBATAN KERJA DAN KOMUNIKASI INTERNAL BAGI KEPUASAN KERJA YAYASAN MANBAUL ULUM - Mafriningsih, Evi (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study aims to analyze the influence of employee involvement and internal communication on job satisfaction at Yayasan Manbaul Ulum. The research method employed is an associative method with a quantitative approach. The entire population of 32 employees was used as the research sample through the saturated sampling technique. The data were collected using questionnaires with a Likert scale applied to all research variables. Data analysis was conducted with the assistance of the IBM SPSS Statistics program. The results indicate that employee involvement has a positive and significant effect on job satisfaction, and internal communication also demonstrates a positive and significant effect. Furthermore, the simultaneous test results show that employee involvement and internal communication jointly have a significant influence on job satisfaction. Therefore, the proposed research hypotheses are accepted, and it can be concluded that employee involvement and internal communication play an important role in improving job satisfaction.